Integrasi Data Untuk Pemodelan 3D Interior dan Eksterior Masjid Al-Syuro Cipari - Jouristiany; Gusti Ayu Jessy Kartini (Jurnal Serambi Engineering, 2025)
Accurate and comprehensive documentation is required for the long-term conservation of heritage buildings. This study aims to integrate the interior and exterior data of the Al-Syuro Cipari Mosque using 3D modelling and a combination of terrestrial laser scanning (TLS) and handheld laser scanning (HLS). Two integration methods were compared — free-net and independent georeferencing — to determine the most effective approach. Data was acquired using a Leica RTC360 TLS for exterior areas and a Leica BLK2GO HLS for hard-to-reach interior areas, particularly the ablution area and the mosque tower. The results showed that both methods successfully integrated the interior and exterior data without any gaps in the transition zones where the architectural elements were clearly defined. Free-net georeferencing produced models with an RMSE of 0.003 m and 66% overlap, whereas independent georeferencing offered greater processing flexibility, albeit with the need for special attention to be paid to systematic errors. Statistical tests revealed no significant discrepancies between the actual dimensions of the objects and the point cloud models in either method. The resulting integrated 3D model can be used to document, maintain and conserve heritage buildings with adequate geometric accuracy.